Enzyme-Based Solid-Phase Electrochemiluminescence Sensors with Stable, Anchored Emitters for Sensitive Glucose Detection - Chunyin Wei; Yanyan Zheng; Fei Yan; Lifang Xu (Biosensors)
Glucose (Glu) detection, as a fundamental analytical technique, has applications in medical diagnostics, clinical testing, bioanalysis and environmental monitoring. In this work, a solid-phase electrochemiluminescence (ECL) enzyme sensor was developed by immobilizing the ECL emitter in a stable manner within bipolar silica nanochannel array film (bp-SNA), enabling sensitive glucose detection. The sensor was constructed using an electrochemical-assisted self-assembly (EASA) method with various siloxane precursors to quickly modify the surface of indium tin oxide (ITO) electrodes with a bilayer SNA of different charge properties. The inner layer, including negatively charged SNA (n-SNA), attracted the positively charged ECL emitter tris(2,2′-bipyridyl)ruthenium(II) (Ru(bpy)32+) via electrostatic interaction, while the outer layer, including positively charged SNA (p-SNA), repelled it, forming a barrier that efficiently concentrated the Ru(bpy)32+ emitter in a stable manner. After modifying the amine groups on the p-SNA surface with aldehyde groups, glucose oxidase (GOx) was covalently immobilized, forming the enzyme electrode. In the presence of glucose, GOx catalyzed the conversion of glucose to hydrogen peroxide (H2O2), which acted as a quencher for the Ru(bpy)32+/triethanolamine (TPA) system, reducing the ECL signal and enabling quantitative glucose analysis. The sensor exhibited a wide linear range from 10 μM to 7.0 mM and a limit of detection (LOD) of 1 μM (S/N = 3). Glucose detection in fetal bovine serum was realized. By replacing the enzyme type on the electrode surface, this sensing strategy holds the potential to provide a universal platform for the detection of different metabolites.